A randomised, controlled trial evaluating a low cost, 3D‐printed bronchoscopy simulator1. (12th June 2017) - Pedersen, T. H.; Gysin, J.; Wegmann, A.; Osswald, M.; Ott, S. R.; Theiler, L.; Greif, R.
Summary: Low‐fidelity, simulation‐based psychomotor skills training is a valuable first step in the educational approach to mastering complex procedural skills. We developed a cost‐effective bronchial tree simulator based on a human thorax computed tomography scan using rapid‐prototyping (3D‐print) technology. This randomised, single‐blind study evaluated how realistic our 3D‐printed simulator would mimic human anatomy compared with commercially available bronchial tree simulators (Laerdal ® Airway Management Trainer with Bronchial Tree and AirSim Advance Bronchi, Stavanger, Norway). Thirty experienced anaesthetists and respiratory physicians used a fibreoptic bronchoscope to rate each simulator on a visual analogue scale (VAS) (0 mm = completely unrealistic anatomy, 100 mm = indistinguishable from real patient) for: localisation of the right upper lobe bronchial lumen; placement of a bronchial blocker in the left main bronchus; aspiration of fluid from the right lower lobe; and overall realism. The 3D‐printed simulator was rated most realistic for the localisation of the right upper lobe bronchial lumen (p = 0.002), but no differences were found in placement of a bronchial blocker or for aspiration of fluid (p = 0.792 and p = 0.057) compared with using the commercially available simulators. Overall, the 3D‐printed simulator was rated most realistic (p = 0.021). Given the substantially lower costs for the 3D‐printed simulator (£85 (€100/US$110) compared with > ~ £2000 (€2350/US$2590) for the commercially available simulators), our 3D‐printed simulator provides an inexpensive alternative for learning bronchoscopy skills, and offers the possibility of practising procedures on patient‐specific models before attempting them in clinical practice.